Effectiveness of progressive mobilization level I on hemodynamic status of stroke patients in the ICU - Yunie Atrie, Utari; Widiastuti , Linda; Siagian, Yusnaini; Wati, Liza; Rahman, Zakiah (University of Muhammadiyah Malang, 2024)
Introduction: Most stroke patients in the ICU to experience very long immobilization and are only able to rest in bed due to decreased consciousness and physical weakness. However, prolonged bed rest in the ICU can have negative impacts on patients, one of which is changes in the patient's hemodynamics. Progressive mobilization has the potential to affect hemodynamic status and has received significant attention in the critical care setting. Objectives: This study aims to determine the effect of progressive mobilization level I on the hemodynamic status of stroke patients in ICU at Bintan Regional Hospital. Methods: The research design was a non-equivalent control group design. The sample size was 32 stroke patient respondents consisting of 16 intervention groups and 16 control groups, with a purposive sampling technique. Measurements were made using observation sheets to assess hemodynamic status before and after progressive mobilization. Results: The results of the bivariate analysis using the Paired T-Test showed that there was a difference in the average heart rate (p=0.000), systolic blood pressure (p=0.003), diastolic blood pressure (p=0.000), respiratory rate (p=0.000), and oxygen saturation (SaO2) (p= 0.001) between before and after progressive mobilization level I. The results of the Independent-T-Test showed that there was an effect of progressive mobilization level I on the hemodynamic status of ICU patients (p= 0.000 for each hemodynamic). There was an increase in hemodynamic status within the normal range after progressive mobilization. Conclusions: The results of this study can be a recommendation for nurses to carry out progressive mobilization level I by paying attention to the hemodynamic status of critical patients, especially for stroke patients to improve quality of life.